High‐Performance, Solution‐Processed, and Insulating‐Layer‐Free Light‐Emitting Diodes Based on Colloidal Quantum Dots. Issue 28 (28th May 2018) - Zhang, Zhenxing; Ye, Yuxun; Pu, Chaodan; Deng, Yunzhou; Dai, Xingliang; Chen, Xiaopeng; Chen, Dong; Zheng, Xuerong; Gao, Yuan; Fang, Wei; Peng, Xiaogang; Jin, Yizheng
Abstract: Quantum‐dot light‐emitting diodes (QLEDs) may combine superior properties of colloidal quantum dots (QDs) and advantages of solution‐based fabrication techniques to realize high‐performance, large‐area, and low‐cost electroluminescence devices. In the state‐of‐the‐art red QLED, an ultrathin insulating layer inserted between the QD layer and the oxide electron‐transporting layer (ETL) is crucial for both optimizing charge balance and preserving the QDs' emissive properties. However, this key insulating layer demands very accurate and precise control over thicknesses at sub‐10 nm level, causing substantial difficulties for industrial production. Here, it is reported that interfacial exciton quenching and charge balance can be independently controlled and optimized, leading to devices with efficiency and lifetime comparable to those of state‐of‐the‐art devices. Suppressing exciton quenching at the ETL–QD interface, which is identified as being obligatory for high‐performance devices, is achieved by adopting Zn0.9 Mg0.1 O nanocrystals, instead of ZnO nanocrystals, as ETLs. Optimizing charge balance is readily addressed by other device engineering approaches, such as controlling the oxide ETL/cathode interface and adjusting the thickness of the oxide ETL. These findings are extended to fabrication of high‐efficiency green QLEDs without ultrathin insulating layers. The work may rationalize the design and fabrication of high‐performance QLEDs without ultrathin insulating layers, representing a step forward to large‐scale production and commercialization. Abstract : Interfacial exciton quenching and charge balance are independently controlled and optimized in quantum‐dot light‐emitting diodes without ultrathin insulating layers, leading to red devices with efficiency (peak external quantum efficiency: 18.2%) and lifetime ( T 50 at an initial brightness of 100 cd m −2 : ≈190 000 h) comparable to those of state‐of‐the‐art devices.